News and views on ion channels in cancer: is cancer a channelopathy? - Bell, Damian C.; Leanza, Luigi; Gentile, Saverio; Sauter, Daniel R. (Frontiers in Pharmacology, 2023)
Ion channels are key signaling proteins found throughout the body; they are critical in many, wide-ranging physiological processes, from gene expression, sensory perception and processing to the cardiac action potential. When ion channel activity goes awry, for example, via mutation, damage or disrupted homeostasis, the outcome can result in causation, development and/or maintenance of disease. Ion channel dependent diseases have been dubbed channelopathies. Recent studies on the role of ion channels in cancer biology suggest that cancer is one such channelopathy. Many ion channels have now been implicated in the cellular processes that are affected in a multitude of cancers. In the last two decades, the field of ion channel and cancer research has been growing exponentially: a combination of developments in molecular biology, genetics, electrophysiology and automation have driven an explosion in our capabilities to interrogate ion channel pathways; how, why and where they go wrong and therapeutic interventions to correct their pathophysiology in cancer. A review of this vast and rapidly developing field would require a titanic tome to merely dimple the surface of research that has ballooned recently. In lieu of that huge undertaking—for the benefit of both authors and readers - this review discusses select examples of primary, applied and clinical research, aiming to shine a light on some of the more innovative and novel findings that this exciting field is excavating.